Anxiety levels and sleep quality in nursing students during the COVID‐19 pandemic. Issue 4 (7th May 2021) - Köktürk Dalcalı, Berna; Durgun, Hanife; Taş, Ayşe Sinem
Abstract: Purpose: This study was carried out with the aim of determining the correlation between the levels of anxiety experienced by students and their sleep quality during the coronavirus disease 2019 (COVID‐19) pandemic. Design and Methods: This descriptive and correlational type study' sample population was 283 students. The personal information form, state‐trait anxiety inventory, Verran and Snyder–Halpern sleep scale were used in data collection. Findings: Study findings indicate that students' state‐trait anxiety levels and sleep quality are average, 28.26% of them sleep interrupted and there is a correlation between their anxiety and sleep quality. Practice Implication: İt is recommended that teaching students how to deal with COVID−19 and interventional studies aimed at improving sleep quality by reducing anxiety levels should be conducted to further investigate the topic.